If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -18n = 75 Combine like terms: 3n + -18n = -15n -15n = 75 Solving -15n = 75 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '-15'. n = -5 Simplifying n = -5
| 4x=3x^2-9x | | h=3vt+12t^2 | | y/5=21 | | 10x+12-6x+20=0 | | 3t^4-8t^3-18t^2-240t=0 | | R/26=14 | | -3.6=z-6.8 | | 8a-2(a-5)=52 | | 3(x-y)dx+5xdy=0 | | 2x+42+2x=360 | | x+0.63(x+0.01)=0.0437 | | 6e^5x=4 | | 5xn=0.36 | | x+27+97+100+60=360 | | x^4-4x^3+6x^2+4x-7=0 | | 26(2)+49=79 | | 19x-69+x+89+9x+79=360 | | x(3-x)-5x=8-(x+2) | | 2m^2+7-30=0 | | 2x-44+x+74+x+82=360 | | x+53+x+95+53+53=360 | | x+0.60(x+0.01)=0.0482 | | 2(x+4)+x=20 | | 5-7s=6s | | 13=4(x+3)+1 | | x^2=18d+80 | | x+0.59(x+0.01)=0.0484 | | 2x+35=x-15 | | 10(s-10)=-167 | | 2r+6s=36 | | 8n-(-2)=7 | | -1(x^2-2x-35)=0 |